THE USE OF TASK BASED LANGUAGE TEACHING (TBLT) AS TO IMPROVE DESCRIPTIVE WRITING SKILLS - Inayanti, Inayanti; Halimi, Sisilia Setiawati, Dr. (UI Scholars Hub, 2019)
Writing skills are one of the skills that must be mastered by language learners. As an effort to improve writing skills, the researcher uses the Task Based Language Teaching (TBLT) approach. The TBLT approach is carried out on 19 level 1 students of the English Literature study program in learning descriptive writing skills in English. The type of research conducted is Classroom Action Research (CAR) in collaboration with lecturers of Writing 1 class. The research is supported by qualitative and quantitative data to determine the students’ improvement in the process of learning descriptive writing using TBLT. The results show a significant increase in the results of descriptive writing tests conducted in the first and second cycles. In addition, the use of TBLT can motivate students in the learning process. The results of this study were obtained based on the grades of the descriptive writing tests, observations and questionnaires. The results of the post-test indicate an increase in the average student score to 85.6 from the average pre-test score of 62.2. Finally, the results of the questionnaire also show that almost all students agreed to use TBLT as a guide in Descriptive writing, and it has proven to be able to improve the students’ writing skills.